Design and analysis of super twisting sliding mode control for machine tools - Chiew, Tsung Heng; Jamaludin, Zamberi; Bani Hashim, Ahmad Yusairi; Rafan, Nur Aidawaty; Abdullah, Lokman; Salleh, Mohd Rizal; Arep @ Ariff, Hambali (Penerbit UTM Press, 2016)
High demands of precision on machine tools are hardly cope by using existing classic control algorithms. This paper focuses on the design, analysis and validation of a super twisting sliding mode controller on a single axis direct drive positioning system for improved tracking performances. The second order positioning system parameters were determined using input and output of measured data. Effects of two gain parameters in control algorithm on the quality of the control input and tracking error were analysed experimentally. The gain parameters were selected based on magnitude reduction in chattering during practical application. The performance of tuned super twisting sliding mode controller was compared with a traditional sliding mode controller using sigmoidlike function. Results showed that super twisting sliding mode controller reduced the chattering effect and improved the performance of system in terms of tracking error by 16.5%.